2022
DOI: 10.1101/2022.07.22.22277842
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA methylation clock DNAmFitAge shows regular exercise is associated with slower aging and systemic adaptation

Abstract: DNAmPhenoAge, DNAmGrimAge, and the newly developed DNAmFitAge are DNA methylation (DNAm) based biomarkers that reflect the individual aging process. Furthermore, physical fitness is known to relate to the aging process, but its relationship to the gut microbiome has not yet been studied. Here, we examine the relationship among physical fitness, DNAm based biomarkers, and the microbiome in adults aged 33-88 with a wide range of physical fitness (including athletes with long-term training history). Higher levels… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 53 publications
(70 reference statements)
0
12
0
Order By: Relevance
“…In addition, comparisons across the tertiles indicated that GrimAgeAccel in the high VO2/kg at Peak groups (31.5 ± 3.3 mL/kg/min) decelerated by approximately 1.6 years, compared to that of low group (21.8 ± 1.9 mL/kg/min) (Figure 2e, Table S4). Similarly, in the recent report, a study of 303 men and women aged 33-88 years, including participants in the World Rowing Masters Regatta in Velence, Hungary, showed that DNAmAgeAccel (i.e., FitAgeAccel) was decelerated by 1.5 years in women and 2.0 years in men in the group with higher indirectly calculated VO2max levels (Women: 42.5 ± 7.5 mL/kg/min; Men: 50.2 ± 10.0 mL/kg/min) compared to those with medium-low group (Women: 28.1 ± 5.4 mL/kg/min; Men: 35.1 ± 6.1 mL/kg/min) (Jokai et al, 2022). Although both studies differ in terms of participants, age range, race, and fitness levels, these findings suggest that retaining a high cardiorespiratory fitness is associated with slowing down the biological aging process.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…In addition, comparisons across the tertiles indicated that GrimAgeAccel in the high VO2/kg at Peak groups (31.5 ± 3.3 mL/kg/min) decelerated by approximately 1.6 years, compared to that of low group (21.8 ± 1.9 mL/kg/min) (Figure 2e, Table S4). Similarly, in the recent report, a study of 303 men and women aged 33-88 years, including participants in the World Rowing Masters Regatta in Velence, Hungary, showed that DNAmAgeAccel (i.e., FitAgeAccel) was decelerated by 1.5 years in women and 2.0 years in men in the group with higher indirectly calculated VO2max levels (Women: 42.5 ± 7.5 mL/kg/min; Men: 50.2 ± 10.0 mL/kg/min) compared to those with medium-low group (Women: 28.1 ± 5.4 mL/kg/min; Men: 35.1 ± 6.1 mL/kg/min) (Jokai et al, 2022). Although both studies differ in terms of participants, age range, race, and fitness levels, these findings suggest that retaining a high cardiorespiratory fitness is associated with slowing down the biological aging process.…”
Section: Discussionmentioning
confidence: 85%
“…Epigenome-wide DNA methylation was measured using the same procedure as previously reported (Jokai et al, 2022). Briefly, genomic DNA bisulfite conversion was performed by using the EZ DNA Methylation Kit (Zymo Research, Irvine, CA, USA), followed by hybridization using Infinium MethylationEPIC BeadChip Kit (Illumina Inc., San Diego, CA, USA).…”
Section: Dna Extraction and Epigenome-wide Dna Methylation Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased arterial stiffness, measured by impedance cardiography, has been shown to associate with an increase in epigenetic age acceleration 19 , validating our finding. Estimation of VO2max has been shown to negatively associate with a fitness specific DNAm clock, FitAge 60 , but not PhenoAge acceleration 61 . This speaks to a hypothesis that different epigenetic clocks capture different portions of aging.…”
Section: Discussionmentioning
confidence: 98%